Analysis Determinants of Human Development Index in Bali Province - Lucky Saputra; Marseto Marseto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research investigates the relationship between fiscal decentralization, economic growth, and income inequality (measured by the Gini ratio) on the Human Development Index (HDI) in regencies and cities within Bali Province during the 2013–2023 period. Human development is a crucial indicator of regional welfare, and understanding the factors that shape HDI is essential for designing effective regional development policies. A quantitative approach was employed through panel data regression, utilizing secondary data sourced from the Central Bureau of Statistics (BPS). The findings indicate that fiscal decentralization has a positive and significant effect on HDI, suggesting that greater regional fiscal authority can improve public service delivery and social welfare. Conversely, economic growth demonstrates a significant negative relationship with HDI, which implies that growth alone does not automatically translate into improved human development, particularly when it is unevenly distributed. In addition, income inequality shows a negative and significant effect on HDI, confirming that disparities in income hinder broader improvements in welfare. Collectively, these variables significantly explain variations in HDI across regencies and cities in Bali. The policy implications emphasize the need to strengthen regional fiscal capacity, reduce income inequality, and encourage inclusive economic growth to ensure that economic progress contributes effectively to enhancing human development.